Red light activated “caged” reagents for microRNA research - Meyer, Andreas; Schikora, M.; Starkuviene-Erfle, Vytaute; Mokhir, A. (Photochemical & photobiological sciences, 2016)
“Caged” reagents for miRNA research (siRNA targeting EGFR, involved in miRNA maturation, and mimics of miR-20a, playing a key role in tumor formation and metastasis) were prepared. It was demonstrated that these reagents can be activated by non-toxic to cells red light both in cells and in cell free settings.
Gesehen am 30.04.2020